A Commentary on TDP-43 and DNA Damage Response in Amyotrophic Lateral Sclerosis. (October 2019) - Mitra, Joy; Hegde, Muralidhar L
Amyotrophic lateral sclerosis (ALS) is a devastating, motor neuron degenerative disease without any cure. About 95% of the ALS patients feature abnormalities in the RNA/DNA-binding protein, TDP-43, involving its nucleo-cytoplasmic mislocalization in spinal motor neurons. How TDP-43 pathology triggers neuronal apoptosis remains unclear. In a recent study, we reported for the first time that TDP-43 participates in the DNA damage response (DDR) in neurons, and its nuclear clearance in spinal motor neurons caused DNA double-strand break (DSB) repair defects in ALS. We documented that TDP-43 was a key component of the non-homologous end joining (NHEJ) pathway of DSB repair, which is likely the major pathway for repair of DSBs in post-mitotic neurons. We have also uncovered molecular insights into the role of TDP-43 in DSB repair and showed that TDP-43 acts as a scaffold in recruiting the XRCC4/DNA Ligase 4 complex at DSB damage sites and thus regulates a critical rate-limiting function in DSB repair. Significant DSB accumulation in the genomes of TDP-43-depleted, human neural stem cell-derived motor neurons as well as in ALS patient spinal cords with TDP-43 pathology, strongly supported a TDP-43 involvement in genome maintenance and toxicity-induced genome repair defects in ALS. In this commentary, we highlight our findings that have uncovered a link between TDP-43 pathology and impaired DNA repair and suggest potential possibilities for DNA repair-targeted therapies for TDP-43-ALS.